Remembering Our Relations Dënesųłıné Oral Histories of Wood Buffalo National Park - Trimble, Sabina (University of Calgary Press, 2023)
Wood Buffalo National Park is located in the heart of Dénesųłıuné homelands, where Dene people have lived from time immemorial. Central to the creation, expansion, and management of this park, Canada 's largest at nearly 45, 000 square kilometers, was the eviction of Dénesųłıuné people from their home, the forced separation of Dene families, and restriction of their Treaty rights. Remembering Our Relations tells the history of Wood Buffalo National Park from a Dene perspective and within the context of Treaty 8. Oral history and testimony from Dene Elders, knowledge-holders, leaders, and community members place Dénesųłıuné voices first. With supporting archival research, this book demonstrates how the founding, expansion, and management of Wood Buffalo National Park fits into a wider pattern of promises broken by settler colonial governments managing land use throughout the twentieth and twenty-first centuries. By prioritizing Dénesųłıuné histories Remembering Our Relations deliberately challenges how Dene experiences have been erased, and how this erasure has been used to justify violence against Dénesųłıuné homelands and people. Amplifying the voices and lives of the past, present, and future, Remembering Our Relations is a crucial step in the journey for healing and justice Dénesųłıuné peoples have been pursuing for over a century.